Analisis Studi Kelayakan Bisnis Pada Usaha Ulap Doyo Pokant Takaq Di Tenggarong Dilihat Dari Aspek Finansial - Rutmaida Butar Butar; Yonathan Palinggi; Kartina Eka Ningsih (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
The purpose of this study was to identify and analyze the feasibility study of Doyo Pokant Takaq's Ulap Business in Tenggarong in terms of financial analysis. The analytical tools used are net present value (NPV), internal rate of return (IRR), net benefit cost ratio (BCR), and payback period. Results Based on the business feasibility analysis, the net present value (NPV) of the Doyo Pokant Takaq Tenggarong Ulap Business was Rp. 526,828,701. The net present value (NPV) was analyzed by the cash flow method for eight years with a DF of 14% so that each year a different cash value was obtained. In the eighth year, the final Net Present Value (NPV) is positive > 0, and this value is still greater than the investment value that has been invested by the owner of the Doyo Pokant Takaq Ulap Business in Tenggarong of Rp. 450,000,000. Because the NPV value is greater than zero, the Do Pokant Takaq Ulap business is still feasible to maintain. The value of the benefit-cost ratio (BCR) is 1.249. The BCR value means that the value of the benefits obtained in the Doyo Pokant Takaq Ulap business in Tenggarong is 1,249 times the value of the costs incurred at an interest rate of 14%. The value of the internal rate of return (IRR) is 33.40%. Because this value is greater than 14%, it can be said that the Doyo Pokant Takaq Ulap business in Tenggarong is feasible. From the results of the analysis of the investment that has been made by Doyo Pokant Takaq's Ulap Business in Tenggarong, it turns out that it can be returned in only 6 years and 10 months. The payback period achieved is only 68% of the 5 years estimated by the business owner to be able to return the existing capital.